2004
DOI: 10.1175/1520-0450(2004)043<1069:ibisrm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inversion Breakup in Small Rocky Mountain and Alpine Basins

Abstract: Comparisons are made between the postsunrise breakup of temperature inversions in two similar closed basins in very different climate settings, one in the eastern Alps and one in the Rocky Mountains. The small, highaltitude, limestone sinkholes have both experienced extreme temperature minima below Ϫ50ЊC and both develop strong nighttime inversions. On undisturbed clear nights, temperature inversions reach to 120-m heights in both sinkholes but are much stronger in the drier Rocky Mountain basin (24 vs 13 K). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 35 publications
2
43
0
6
Order By: Relevance
“…16) and 25 August ( here, but aspects such as Bowen ratio, stability (Whiteman et al 2004) and the mixing of momentum from the top of the valley (Egger 1990) are expected to be of importance in this context.…”
Section: Total Heat Budget a Time Evolution Of The Valley Heat Budgetmentioning
confidence: 93%
“…16) and 25 August ( here, but aspects such as Bowen ratio, stability (Whiteman et al 2004) and the mixing of momentum from the top of the valley (Egger 1990) are expected to be of importance in this context.…”
Section: Total Heat Budget a Time Evolution Of The Valley Heat Budgetmentioning
confidence: 93%
“…Feld et al (2013) observed that the empirical relationship from historical observations has limited reliability in the future due to expected changes in the atmospheric moisture in a changing climate. As mountain climate is a balance between free air advective processes and surface radiative effects (Whiteman et al, 2004;Pepin and Lundquist, 2008), understanding the complex nuances of orographic controls on the Himalayan climate system is a priority for this region with limited data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Al centrar los estudios en época reciente, se establecen investigaciones entre el otoño 2001 y el verano de 2012, donde se estudian los mecanismos de formación y ruptura de piscinas de aire frío en las dolinas del Gstettneralm (Pospichal et al, 2003;Whiteman et al, 2004) y las de Peter Sinks en Utah (Clements et al, 2003). Concluyeron que, durante las noches despejadas, en el interior de las dolinas las tasas de enfriamiento son más importantes tras la puesta del sol, mientras que el enfriamiento es más gradual durante la noche y posterior madrugada.…”
Section: Introductionunclassified